2015
DOI: 10.1038/srep18462
|View full text |Cite
|
Sign up to set email alerts
|

Cancer associated missense mutations in BAP1 catalytic domain induce amyloidogenic aggregation: A new insight in enzymatic inactivation

Abstract: BRCA1 associated protein 1 (BAP1) is a nuclear deubiquitinase that regulates tumor suppressor activity and widely involves many cellular processes ranging from cell cycle regulation to gluconeogenesis. Impairment of enzymatic activity and nuclear localization induce abnormal cell proliferation. It is considered to be an important driver gene, which undergoes frequent mutations in several cancers. However the role of mutation and oncogenic gain of function of BAP1 are poorly understood. Here, we investigated ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 61 publications
4
37
0
Order By: Relevance
“…While the role of protein aggregation has been extensively studied in the context of proteostasis and neurodegenerative diseases, the observations reported in the Supporting Information Table S1 show that protein misfolding and aggregation are associated with several other types of human maladies. Consistent with these observations, evidence suggesting a role for aggregation in cancer is emerging . However, a potential role for protein aggregation in cardiovascular diseases needs to be investigated further.…”
Section: Resultsmentioning
confidence: 75%
“…While the role of protein aggregation has been extensively studied in the context of proteostasis and neurodegenerative diseases, the observations reported in the Supporting Information Table S1 show that protein misfolding and aggregation are associated with several other types of human maladies. Consistent with these observations, evidence suggesting a role for aggregation in cancer is emerging . However, a potential role for protein aggregation in cardiovascular diseases needs to be investigated further.…”
Section: Resultsmentioning
confidence: 75%
“…BAP1 (ubiquitin carboxyl-terminal hydrolase) is a deubiquitinase that acts as a tumor suppressor. Cancer-associated mutations within this gene were found to destabilize protein structure promoting β-amyloid aggregation in vitro, which is the pathological hallmark in Alzheimer’s disease 33 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, inactivating mutations within the gene, including insertions, deletions, frameshift, nonsense and missense mutations, have all been reported 11. Studies have shown that the tumour suppressor effects of BAP1 depend on both deubiquitinating activity and nuclear localisation, typically lost by missense mutations and truncating mutations, respectively 10.…”
Section: Bap1 Gene Mutationsmentioning
confidence: 99%
“…Cancer-associated missense mutations in the UCH domain of BAP1 can lead to structural instability and β-amyloid aggregation in vitro. Aggregates of BAP1 accumulate in the cytoplasm and upregulate heat shock protein response, specifically with increased expression of Hsp90, which is known to be overexpressed in cancers 11. Furthermore, ubiquitin-conjugating enzyme UBE2O ubiquitinates the NLS of BAP1, resulting in its cytoplasmic sequestration.…”
Section: Bap1 Gene Mutationsmentioning
confidence: 99%